On calculation of linear resource planning models for optimal project scheduling - Valuev, Andrey (Mathematical Modelling and Analysis, 2008)
Recent author's papers have shown new opportunities resulting from the treatment of resource planning in project scheduling as the optimization problem for a hybrid system. This approach gives the possibility to work out the optimum resource sharing in an iteration process of branch‐and‐bound type. The present paper concentrates on the most standard case of the problem in question for which all the relationships may be represented in the linear form. Two exact finite methods are proposed. The first method is obtained using the piecewise‐linear form of Bellman function, the second evolves from the decomposition approach for dynamic linear programming problem.First Published Online: 14 Oct 2010